Development of the Flexibility in Daily Life scale to measure multidimensional cognitive and behavioural flexibility in health and disease. - Horne, Kristina; Chen, Tao; Irish, Muireann (British Journal of Clinical Psychology, 2025)
Objectives: Inflexibility of thought and behaviour is a transdiagnostic feature of many neuropsychiatric disorders and presents several empirical measurement challenges. Here, we developed and validated the Flexibility in Daily Life scale (FIDL); a novel, self‐report questionnaire, which captures expressions of cognitive and behavioural flexibility in daily life and is sensitive to natural shifts in these processes across the adult lifespan. Methods: The FIDL was developed using a deductive scale development approach, which aimed to capture common themes within the flexibility literature and across diagnoses (e.g. insistence on sameness, preference for routines). Following multidisciplinary consensus, an initial 37‐item questionnaire was submitted for validation in an online sample of 295 healthy adult participants (19–78 years). Results: Exploratory factor analysis produced a revised 21‐item version comprising five factors, labelled: Repetition, Switching, Predictability/Control, Routine, and Thoughts/Beliefs. Internal consistency reliability was good‐to‐strong for the total FIDL score and moderate‐to‐strong for individual subscales. Convergent validity was established between the FIDL and an existing measure of cognitive flexibility. Critically, the FIDL total score evinced a U‐shaped relationship with age, whereby flexibility was lower at the younger and older tails of the lifespan and greater in middle age. The same U‐shaped trajectory emerged for the Repetition, Routine, and Thoughts/Beliefs factors. Conclusions: Overall, the FIDL is a valid and reliable multidimensional measure of flexibility, which upholds a clearly defined factor structure and good psychometric properties. It promises to be a valuable clinical and research tool to assess the natural fluctuations in flexibility across the lifespan and departures thereof.